Social context modulates active avoidance: Contributions of the anterior cingulate cortex in male and female rats. - Ruble, Shannon; Payne, Karissa; Kramer, Cassandra; West, Lexe; Ness, Halle; Erickson, Greg; Scott, Alyssa; Diehl, Maria M. (Elsevier, 2024)
Actively avoiding danger is necessary for survival. Most research on active avoidance has focused on the behavioral and neurobiological processes when individuals learn to avoid alone, within a solitary context. Therefore, little is known about how social context affects active avoidance. Using a modified version of the platform-mediated avoidance task in rats, we investigated whether the presence of a social partner attenuates conditioned freezing and enhances avoidance compared to avoidance in a solitary context. Rats spent a similar amount of time avoiding during either context; however, rats trained in the social context exhibited greater freezing as well as lower rates of darting and food seeking compared to rats trained in the solitary context. In addition, we observed higher levels of avoidance in females compared to males in the solitary context, but this sex difference was not present in rats trained in the social context. To gain greater mechanistic insight, we optogenetically inactivated glutamatergic projection neurons in the anterior cingulate cortex (ACC) following avoidance training in either context. After avoidance was learned in a social context, photoinactivation of ACC reduced expression of avoidance during a test when the social partner was absent, but not when the partner was present. Our findings suggest a novel contribution of the ACC in avoidance that is learned with a social partner, which has translational implications for understanding ACC dysfunction in those suffering from trauma-related disorders.
Keywords: Prefrontal cortex; Fear; Sex differences; Optogenetics